Synthesis and Characterization of Activated Carbon from Pattikala Fruit Waste (Etlingera elatior) - Rahmawati, Hilda; Ismail, Nurmalasari; Asriyani, Nur; Jufri, Risma (Journal of Energy, Material, and Instrumentation Technology, 2024)
Activated carbon (AC) is an amorphous material with a suitable size pores distribution, high specific surface area, and high surface reactivity. Activated carbon can be produced from biomaterials and can be used as a water filter material, an absorbent for hazardous substances, and as electrodes in supercapacitors. Etlingera elatior or Pattikala fruit waste has lignocellulose content that can potentially be activated carbon material. This study aimed to synthesize Etlingera elatior or Pattikala fruit waste by chemical activation method into activated carbon. Based on the study's results, activated carbon from Pattikala fruit waste has a high purity level of 87.80%, and SEM results show that pores have begun to form in the activated carbon samples produced. This study demonstrates that activated carbon can be produced from Etlingera elatior fruit waste.